Splash-proof anhydrous taphole mud and preparation method thereof

Through the synergistic effect of zirconium oxide sol-modified phenolic resin and gradient mullite-coated SiC particles, the problems of traditional anhydrous taphole mud's attenuated bonding strength and weak interface bonding at high temperatures are solved, excellent thermal shock resistance and slag erosion resistance at high temperatures are achieved, and molten iron penetration and splashing are effectively suppressed.

CN120423861BActive Publication Date: 2025-09-12LUOYANG SHENG TIE REFRACTORY MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510932965.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-08
Publication Date
2025-09-12
Estimated Expiration
2045-07-08

AI Technical Summary

Technical Problem

The binder of traditional anhydrous taphole mud is easily pyrolyzed at high temperature, the bonding strength drops sharply, and the interface bonding is weak, which makes it difficult to cure the molten iron penetration and splashing phenomenon.

Method used

Zirconia sol-modified phenolic resin and gradient mullite-coated SiC particles are used to form a Zr-OC covalent bond network and a gradient mullite coating, which improves high-temperature bonding strength and interfacial bonding strength and hinders slag penetration.

Benefits of technology

It significantly improves the high-temperature performance of anhydrous taphole mud, inhibits molten iron penetration and splashing, extends the life of the taphole plugging, reduces the risk of equipment damage, and improves the safety and efficiency of blast furnace operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention discloses an anti-splash anhydrous taphole mud in the field of refractory materials for iron and steel metallurgy and a preparation method thereof. The raw materials include: anhydrous taphole mud of zirconia sol-modified phenolic resin and gradient mullite-coated silicon carbide particles, and the remaining components are high-alumina bauxite clinker, brown corundum, coke powder, asphalt, a dispersant, and a defoamer. The zirconia sol-modified phenolic resin is prepared by reacting phenol and formaldehyde to form a linear prepolymer, which is then modified by adding an alkali solution, and then reacted by adding zirconium n-butoxide and subjected to reduced pressure distillation. The gradient mullite-coated silicon carbide particles are prepared by using silicon carbide as a matrix, being dispersed in aluminum hydroxide sol, and then being added with ethyl orthosilicate, hydrothermally insulated, and calcined at high temperature. The preparation method includes the steps of dry mixing, wet mixing, pressing, and curing. The taphole mud has high high-temperature bonding strength and good thermal shock resistance, can effectively suppress molten iron splashing, and extend the service life of the taphole.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of refractory materials for iron and steel metallurgy, and in particular to a splash-proof anhydrous taphole mud and a preparation method thereof. Background Art

[0002] Blast furnace taphole sealing is a core application of anhydrous taphole mud in steelmaking, and its performance directly impacts the safety and efficiency of blast furnace operations. Traditional anhydrous taphole mud, composed primarily of high-alumina bauxite and corundum, and phenolic resin or asphalt as a binder, has long been used as a taphole sealing material due to its room-temperature adhesion and limited resistance to slag erosion. However, with the intensification of blast furnace smelting and the increase in molten iron temperatures, the performance shortcomings of traditional taphole mud at high temperatures have become increasingly apparent. At temperatures of 1400-1600°C, phenolic resin readily decomposes and loses weight, causing the bond strength to drop sharply from 5-8 MPa at room temperature to 2-3 MPa at 1000°C, making it unable to inhibit molten iron penetration. The interfacial bonding between the single aggregate and the matrix is ​​weak, and stress concentration during thermal shock easily generates and propagates microcracks, forming channels for molten iron penetration. CaO in the slag reacts with the matrix Al2O3 to form low-melting-point phases (such as anorthite), accelerating structural failure and ultimately causing molten iron splashing, which not only pollutes the environment but also threatens the safety of operators.

[0003] The performance deficiencies of traditional taphole clay stem from the limitations of its material system. For one thing, phenolic resin, the primary binder, lacks high-temperature thermal stability and a low carbon residue, preventing it from forming a continuous high-temperature strength support network. Furthermore, the interface between aggregates (such as SiC and corundum) and the matrix relies on physical intercalation, lacking chemical bonding. This leads to interfacial debonding during thermal shock, creating microcracks. Furthermore, single modification methods (such as adding silane coupling agents or metallic aluminum powder) can only partially improve bonding strength or slag resistance, but cannot synergistically address the issues of high-temperature strength degradation and weak interfacial bonding. Consequently, the spattering phenomenon remains difficult to completely eliminate.

[0004] In response to the above problems, the development of an anhydrous taphole mud with high-temperature bonding strength, interface bonding and slag erosion resistance has become an urgent need in the industry. The present invention introduces two modifying compounds, zirconium oxide sol-modified phenolic resin and gradient mullite-coated SiC particles, to synergistically optimize the high-temperature performance of taphole mud: the former improves the high-temperature carbon residue rate and interface bonding strength of the resin through the Zr-OC covalent bond network, and the latter enhances the aggregate-matrix bonding and inhibits slag penetration through the gradient mullite coating. The synergistic effect of the two modifying compounds effectively solves the problems of high-temperature strength attenuation, weak interface bonding and insufficient slag resistance of traditional taphole mud, and provides a new material solution for the safe and efficient sealing of blast furnace tapholes. Summary of the Invention

[0005] The purpose of the present invention is to provide a splash-proof anhydrous taphole mud and a preparation method thereof, which solves the problem that the binder of traditional anhydrous taphole mud is easily pyrolyzed at high temperature, the bonding strength drops sharply, and it is difficult to inhibit the penetration of molten iron.

[0006] The present invention achieves the above-mentioned purpose through the following technical solutions:

[0007] A splash-proof anhydrous taphole mud comprises the following raw materials in parts by weight:

[0008] Zirconia sol modified phenolic resin: 6-10 parts by weight;

[0009] Gradient mullite-coated SiC particles: 20-30 parts by weight;

[0010] High alumina clinker: 25-35 parts by weight;

[0011] Brown corundum: 10-15 parts by weight;

[0012] Coke powder: 5-10 parts by weight;

[0013] Asphalt: 3-6 parts by weight;

[0014] Dispersant: 0.2-0.5 parts by weight;

[0015] Defoaming agent: 0.3-0.5 parts by weight;

[0016] The preparation method of the zirconium oxide sol-modified phenolic resin comprises the following steps: A1, adding phenol and formaldehyde aqueous solution in a mass ratio of 1:(0.9-1) into a reactor equipped with a reflux condenser, adding NaOH solution under mechanical stirring, heating to 70-72°C to react and obtain a linear phenolic resin prepolymer; A2, adding zirconium n-butoxide to the reactor, adjusting the pH to 5.0-5.5, heating to 90-92°C and stirring for reaction; after the reaction is completed, cooling to room temperature, adding deionized water for dilution, and distilling under reduced pressure.

[0017] According to a preferred embodiment of the present invention, the phenol is purchased from Sinopec Shanghai Petrochemical Co., Ltd., and the model is "industrial grade phenol (SH-01)".

[0018] According to a preferred embodiment of the present invention, the formaldehyde is purchased from Luxi Chemical Group Co., Ltd., and the model is "37% industrial grade formaldehyde solution (LX-02)".

[0019] According to a preferred embodiment of the present invention, the reactor was purchased from Jiangsu Yangyang Chemical Equipment Co., Ltd., and the model number was "500L stainless steel reactor with reflux condenser (YYSR-500)".

[0020] According to a preferred embodiment of the present invention, the NaOH solution was purchased from Hubei Shuanghuan Science and Technology Co., Ltd., and the model number was "20% industrial grade NaOH solution (SH-03)".

[0021] According to a preferred embodiment of the present invention, the zirconium n-butoxide was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and the model number was “zirconium n-butoxide (AR, AL-01)”.

[0022] According to a preferred embodiment of the present invention, the deionized water was purchased from Shanghai Yikang Chemical Co., Ltd., and the model number was "industrial grade deionized water (IK-01)".

[0023] According to a preferred embodiment of the present invention, the high-alumina bauxite clinker is purchased from Shanxi Huaxing Aluminum Co., Ltd., and the model is "85% high-alumina bauxite clinker (block, GH-01)".

[0024] According to a preferred embodiment of the present invention, the brown corundum was purchased from Guizhou Dazhong Seventh Grinding Wheel Factory, and the model number was "95% brown corundum particles (ZG-01)".

[0025] According to a preferred embodiment of the present invention, the coke powder is purchased from Shanxi Coking Coal Group Co., Ltd., and the model is "80% fixed carbon coke powder (-0.075mm, JM-01)".

[0026] According to a preferred embodiment of the present invention, the asphalt is purchased from China National Offshore Oil Corporation, and the model number is "100# medium-temperature asphalt (LQ-01)".

[0027] According to a preferred embodiment of the present invention, the dispersant is purchased from Wanhua Chemical Group Co., Ltd. and the model number is "polycarboxylate dispersant (PC-100)".

[0028] According to a preferred embodiment of the present invention, the defoaming agent is purchased from Dow Corning (China) Investment Co., Ltd. and the model number is "organic silicon defoaming agent (DOW CORNING 200)".

[0029] According to a preferred embodiment of the present invention, in step A1, the mass of the NaOH solution accounts for 2.5-2.8% of the mass of the phenol, the mass percentage concentration of the NaOH solution is 20-25%, and the temperature is raised to 70-72° C. and the reaction time is 40-50 min.

[0030] According to a preferred embodiment of the present invention, in step A2, the zirconium n-butoxide accounts for 4-5% of the mass of the linear phenolic resin prepolymer; the stirring speed is 250-300 rpm; the reaction time is 90-100 min; the temperature of the reduced pressure distillation is 60-70°C, and the pressure is -0.09~-0.095 MPa.

[0031] The preparation of the zirconium oxide sol-modified phenolic resin in the present invention begins with mixing phenol and formaldehyde aqueous solution. Under mechanical stirring and NaOH catalysis, the hydroxyl groups of the phenol and the aldehyde groups of the formaldehyde undergo a condensation reaction to generate a linear phenolic resin prepolymer containing a large number of hydroxymethyl groups. During this process, NaOH acts as a catalyst to neutralize the acidic substances generated by the reaction, promoting the forward progress of the condensation reaction. The reaction temperature is controlled at 70-72°C and maintained for 40-50 minutes to ensure that the prepolymer molecular chains are fully expanded and have sufficient reactive sites. Subsequently, zirconium n-butoxide is added, which slowly hydrolyzes in a weakly acidic environment of pH = 5.0-5.5, releasing sol particles containing Zr-OH. These sol particles react with the hydroxymethyl or unreacted phenolic hydroxyl groups in the prepolymer through condensation to form Zr-OC covalent bonds, so that the ZrO2 sol is evenly anchored on the resin molecular chain in the form of nano-scale particles, forming a stable covalent bond network structure; after the reaction is completed, the temperature is raised to 90-92°C and maintained for 90-100 minutes to promote sufficient cross-linking of the sol and the resin; finally, unreacted free phenol, formaldehyde and by-products (such as methanol) are removed by reduced pressure distillation (60-70°C, -0.09~-0.095MPa) to obtain a modified resin containing uniformly dispersed ZrO2 nanoparticles (particle size ≤10nm), whose pyrolysis rate at high temperature is significantly reduced and the residual carbon rate is improved.

[0032] According to a preferred embodiment of the present invention, the preparation method of the gradient mullite-coated SiC particles includes: B1, dispersing α-SiC particles in Al(OH)3 sol, adding ethyl orthosilicate, and transferring to a hydrothermal reactor after ultrasonic dispersion, and keeping warm at 150-155°C; B2, taking out the particles after hydrothermal treatment and placing them in a muffle furnace at 1000-1050°C for calcination.

[0033] According to a preferred embodiment of the present invention, the α-SiC particles are purchased from Beijing Tianke Heda Semiconductor Co., Ltd., and the model number is "TCS-iC-01 (0.5-1.2 mm grade)".

[0034] According to a preferred embodiment of the present invention, the Al(OH)3 sol is purchased from Jiangsu Sanmu Group Co., Ltd., and the model is "37% aluminum hydroxide sol (SM-02, SiO2 content ≤0.5%)".

[0035] According to a preferred embodiment of the present invention, the tetraethyl orthosilicate was purchased from Hubei Xingfa Chemical Group Co., Ltd., and the model number was "industrial grade tetraethyl orthosilicate (ES-01)".

[0036] According to a preferred embodiment of the present invention, the hydrothermal reactor was purchased from Shanghai Keheng Industrial Development Co., Ltd., and the model number was "KHX-500 stainless steel hydrothermal reactor (volume 500 mL)".

[0037] According to a preferred embodiment of the present invention, the muffle furnace is purchased from Beijing Ingenuity Technology Co., Ltd., and the model is "DK-1000 box-type high-temperature muffle furnace (maximum temperature 1200° C.)".

[0038] According to a preferred embodiment of the present invention, in step B1, the particle size of the α-SiC particles is 0.5-1.2 mm; the SiO2 content in the Al(OH)3 sol is ≤0.5%; the ethyl orthosilicate accounts for 1.5-2% of the SiC mass; the ultrasonic dispersion time is 30-40 min; and the insulation time is 6-8 h.

[0039] According to a preferred embodiment of the present invention, in step B2, the calcination time in the muffle furnace is 2-4 hours.

[0040] In the preparation of the gradient mullite-coated SiC particles of the present invention, α-SiC particles (particle size 0.5-1.2 mm) are first dispersed in Al(OH)3 sol (SiO2 content ≤ 0.5%) to form a stable suspension system; after adding ethyl orthosilicate, it is slowly hydrolyzed in water to form SiO2 sol, and ultrasonic dispersion (30-40 minutes) is performed to make the SiO2 sol uniformly adhere to the surface of the SiC particles to form an amorphous SiO2 transition layer with a thickness of about 2-3 μm; then the material is transferred to a hydrothermal reactor and kept at 150-155°C for 6-8 hours. Under these conditions, the SiO2 and Al in the Al(OH)3 sol react with each other to form a transition layer. 3+ A co-precipitation reaction occurs to generate a mullite (3Al2O3·2SiO2) precursor, which fills the SiO2 transition layer, forming a gradient structure of "SiC-SiO2 transition layer-mullite precursor". After calcination in a muffle furnace at 1000-1050℃ for 2-4 hours, the mullite precursor crystallizes to form stable mullite crystals (3-7μm thick), ultimately obtaining SiC particles with a gradient mullite coating on the surface. The coating is tightly bonded to the SiC substrate without obvious interface defects. In addition, the mullite phase reacts with CaO in the slag at high temperature to generate a high-melting-point calcium feldspar phase, which hinders the formation of a low-melting-point infiltration layer.

[0041] The present invention also provides a method for preparing the splash-proof anhydrous taphole mud, comprising the following steps:

[0042] S1. First, add high-alumina bauxite clinker and brown corundum into a forced mixer and dry mix; then add gradient mullite-coated SiC particles and continue dry mixing;

[0043] S2. Add coke powder and dry mix; heat the zirconium oxide sol-modified phenolic resin to 55-60°C until it melts, mix it evenly with asphalt, add it to the mixer, and wet mix it until the resin completely covers the aggregate and fills the gaps between the particles;

[0044] S3. Finally, add the polycarboxylate dispersant and the silicone defoamer, and stir until the slurry is uniform and free of lumps; inject the stirred material into the mold, press it into shape at a pressure of 15-16 MPa, and solidify it at 180-190°C after demolding.

[0045] According to a preferred embodiment of the present invention, the polycarboxylate dispersant is purchased from Wanhua Chemical Group Co., Ltd. and the model number is "Polycarboxylate Dispersant (PC-100)".

[0046] According to a preferred embodiment of the present invention, the organosilicon defoamer is purchased from Dow Corning (China) Investment Co., Ltd., and the model number is "organosilicon defoamer (DOW CORNING 300)".

[0047] According to a preferred embodiment of the present invention, in step S1, the rotation speed of dry mixing is 80-90 rpm, and the dry mixing time is 5-10 min; the rotation speed of continued dry mixing is 120-140 rpm, and the continued dry mixing time is 8-10 min.

[0048] According to a preferred embodiment of the present invention, in step S2, the dry mixing time is 5-10 min; the mass ratio of zirconium oxide sol-modified phenolic resin to asphalt is (2-2.5):1 and they are mixed evenly; the wet mixing speed is 150-200 rpm and the time is 10-20 min.

[0049] According to a preferred embodiment of the present invention, in step S3, the stirring speed is 200-250 rpm, the stirring time is 3-5 min; the mold size is 40 mm×40 mm×160 mm; and the curing time is 5-8 h.

[0050] In the integrated preparation process of the taphole mud, high-alumina bauxite clinker and brown corundum serve as the primary aggregates, providing an Al2O3 matrix skeleton whose high melting point supports high-temperature structural stability. Coke powder, a carbonaceous component, fills interstices between the aggregates and enhances oxidation resistance. Asphalt and zirconium oxide sol-modified phenolic resin synergistically serve as binders. The former provides adhesion at room temperature, while the latter, through a Zr-OC covalent bond network, delays thermal decomposition at high temperatures, maintaining a high carbon residue rate (≥65%). Together, they form a dual bonding system: "room-temperature bonding and high-temperature carbon residue." Dispersants and defoamers regulate the slurry's fluidity, eliminate bubbles generated during stirring, and ensure uniform dispersion of all components. After dry mixing (pre-mixing at 80-90 rpm, followed by continuous mixing at 120-140 rpm) and wet mixing (at 150-200 rpm), the interfacial bonding between the mullite coating on the surface of the gradient mullite-coated SiC particles, the aggregate, and the matrix is ​​significantly enhanced, forming a continuous "aggregate-coating-matrix" interface structure. During the pressing (15-16MPa) and curing (180-190℃, 5-8 hours) processes, the resin is further cross-linked and cured, and the mullite coating crystal form is more perfect. The final taphole mud exhibits excellent thermal shock resistance, slag erosion resistance and bonding strength at high temperatures (1000-1600℃), effectively inhibiting molten iron penetration and splashing.

[0051] The beneficial effects of the present invention are:

[0052] The present invention significantly improves the high-temperature performance of anhydrous taphole mud through the synergistic effect of two modified compounds, effectively solving the splashing problem caused by the attenuation of high-temperature bonding strength in traditional taphole mud. Among them, the zirconium oxide sol modified phenolic resin forms a stable covalent bond network by introducing zirconium oxide sol and phenolic resin molecular chains, which delays the thermal decomposition weight loss of the binder under high-temperature environment, maintains a high residual carbon rate, and enables the taphole mud to maintain a strong bonding strength above 1000°C; the gradient mullite-coated silicon carbide particles form a continuous ceramic phase network at high temperatures through the gradient distribution of mullite phase on the surface, effectively buffering the thermal stress concentration, reducing the risk of microcrack expansion caused by thermal shock, and significantly improving the thermal shock resistance of the taphole mud.

[0053] The synergistic effect of the two modified compounds further enhances the taphole mud's interfacial bonding and resistance to slag erosion. The covalent bond network of the zirconium oxide sol-modified phenolic resin and the mullite phase of the gradient mullite-coated silicon carbide particles interweave within the matrix, forming a continuous "aggregate-coating-matrix" interface structure. This significantly improves interfacial bonding and avoids the structural collapse of traditional taphole mud caused by interfacial debonding. Simultaneously, the gradient mullite coating reacts at high temperatures with the calcium oxide in the slag to form a high-melting-point calcium feldspar phase, which covers the particle surface and hinders the formation of a low-melting-point permeable layer, reducing the depth of slag erosion on the taphole mud and effectively inhibiting the formation of molten iron permeation channels.

[0054] This synergistic modification system significantly improves the overall performance of taphole clay. Its high-temperature bonding strength, thermal shock resistance, and slag erosion resistance are significantly superior to those of traditional anhydrous taphole clay. It effectively suppresses the penetration and splashing of molten iron during the tapping process. In practical applications, this taphole clay can extend the life of the taphole plugging, reduce equipment damage and material waste caused by splashing, and lower operator safety risks. It provides a reliable material guarantee for the efficient and stable operation of blast furnaces, with significant economic and social benefits. DETAILED DESCRIPTION

[0055] The following specific implementation methods are only used to further illustrate the present application and should not be understood as limiting the scope of protection of the present application. Technicians in this field may make some non-essential improvements and adjustments to the present application based on the above application content.

[0056] Example 1 Weigh 8 g of zirconium oxide sol-modified phenolic resin, 25 g of gradient mullite-coated SiC particles, 30 g of high-alumina bauxite clinker, 12 g of brown corundum, 7 g of coke powder, 5 g of asphalt, 0.3 g of polycarboxylate dispersant, and 0.4 g of silicone defoamer. The specific preparation process is as follows: first, zirconia sol-modified phenolic resin is prepared, 8 g of analytically pure phenol and 7.6 g of 37% formaldehyde aqueous solution (mixed at a phenol:formaldehyde mass ratio of 1:0.95) are weighed and added to a 500 mL stainless steel reactor with a reflux condenser, and mechanical stirring is turned on (speed 200 rpm); NaOH solution (0.21 g, concentration 22%) with a mass ratio of 2.6% of phenol is slowly added to the reactor, and stirred for 5 minutes until completely dissolved. The system temperature naturally rises to 50°C; the temperature is slowly raised to 70°C (heating rate 5°C / min), and this temperature is maintained for 45 minutes (during this period, the system viscosity is measured every 5 minutes with a rotational viscometer. When the viscosity reaches 500-800 mPa·s, it is considered that a linear phenolic resin prepolymer is formed); n-butanol is added to the prepolymer 0.009 g of zirconium was prepared by adjusting the pH to 5.2 with 10% hydrochloric acid (hydrochloric acid was added dropwise until the pH meter showed 5.2±0.1), heating to 91°C (heating rate 3°C / min), and stirring at 250 rpm for 95 min (during which the characteristic absorption peak of the Si-OC bond was monitored by Fourier transform infrared spectrometry to confirm the completion of the modification reaction). After the reaction, the mixture was cooled to room temperature (25°C), diluted with deionized water to a total mass of 1.2 times that of the original prepolymer (about 9.6 g), and transferred to a rotary evaporator. Unreacted phenol, formaldehyde, and by-product methanol were removed by distillation at 65°C and -0.092 MPa for 30 min to obtain 8 g of zirconium oxide sol-modified phenolic resin with a solid content of 80% and a viscosity (25°C) of 900-1200 mPa·s.Next, gradient mullite-coated SiC particles were prepared. 25 g of 0.8 mm α-SiC particles (ball-milled to remove sharp edges) were dispersed in 30 g of Al(OH)3 sol (SiO2 content ≤ 0.5%, solid content 30%). 0.45 g of ethyl orthosilicate was added and ultrasonic dispersion was performed using an ultrasonic disperser (frequency 40 kHz) for 35 min (stirring was paused every 10 min to observe the dispersion uniformity). The dispersed slurry was transferred to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor, sealed, and placed in a thermostat at 152°C. The mixture was heated for 7 h (heating rate 2°C / min, pressure was recorded every 30 min during the holding stage and maintained at 0.8-1.0 MPa); after the reaction was completed, it was naturally cooled to room temperature, the material was taken out and washed with deionized water for 3 times (centrifugal separation after each washing, speed 8000 rpm, time 5 min), the washed particles were placed in a muffle furnace, heated to 1020°C at 5°C / min in an air atmosphere, and calcined for 3 h (keeping at 100°C for 10 min during the heating stage), and finally 25 g of SiC particles with a surface gradient distribution of mullite coating (thickness 5-7 μm) were obtained. Finally, the anti-splash anhydrous taphole mud was prepared. 30g of high-alumina bauxite clinker and 12g of brown corundum were added to a forced mixer (volume 5L) and dry-mixed at 85rpm for 7min (the material was scraped every 2min to ensure uniformity); 25g of gradient mullite-coated SiC particles were added and dry-mixed at 130rpm for 9min (the color uniformity of the material was observed and there was no obvious particle agglomeration); 7g of coke powder (particle size ≤0.075mm) was added and dry-mixed for 6min (a sieve was used to check that there were no particle agglomerates larger than 2mm); 8g of zirconia sol-modified phenolic resin was placed in a 60℃ water bath and heated until completely melted (about 10min), mixed evenly with 5g of asphalt (softening point 105℃) (stirred with a glass rod until no oil droplets were separated), and added to the mixer and wet-mixed at 170rpm for 15min (deionized water was added three times during this period, 5m each time). L, the total amount of water added is 15% of the resin mass, ensuring that the resin completely wraps the aggregate and fills the gaps between the particles. The resin coverage thickness on the particle surface is about 20-30μm when observed under a microscope); 0.3g of polycarboxylate dispersant and 0.4g of silicone defoamer are added, and stirred at a high speed of 220rpm for 4min (during which the viscosity of the slurry is monitored with a viscometer and controlled at 2000-3000mPa·s to ensure molding fluidity); the stirred material is injected into a 40mm×40mm×160mm steel mold (the inner wall is coated with a release agent), and pressed into shape at a pressure of 15MPa (holding time 2min). After demoulding, it is cured in an oven at 185℃ for 6h (heating rate 10℃ / min, and the furnace door is opened every 30min during the curing stage to release moisture). Finally, a splash-proof anhydrous taphole mud with a smooth surface and no obvious pores (average pore size ≤3μm) is obtained.

[0057] Example 2: The specific preparation method is the same as Example 1, except that 6 g of zirconia sol-modified phenolic resin, 20 g of gradient mullite-coated SiC particles, 35 g of high-alumina clinker, 10 g of brown corundum, 10 g of coke powder, 6 g of asphalt, 0.2 g of dispersant, and 0.3 g of defoamer are used. Preparation of the zirconia sol-modified phenolic resin: 6 g of phenol and 5.7 g of formaldehyde aqueous solution are mixed, 0.16 g of NaOH solution (23%) is added, and the mixture is reacted at 70°C for 48 min to obtain a prepolymer. 0.008 g of zirconium n-butoxide is added, the pH is adjusted to 5.1, and the mixture is stirred at 90°C for 98 min. After cooling, the mixture is distilled under reduced pressure (62°C, -0.093 MPa) to obtain 6 g of the modified resin. Preparation of gradient mullite-coated SiC particles: α-SiC particles (20 g, particle size 1.0 mm) were dispersed in Al(OH)3 sol (28 g, SiO2 content 0.4%), 0.4 g of ethyl orthosilicate was added, and the mixture was ultrasonically dispersed for 38 min and kept at 151°C for 6.5 h; calcined at 1030°C for 3.5 h to obtain 20 g of coated particles. Preparation of splash-proof anhydrous taphole mud: dry-mix 35g of high-alumina bauxite clinker and 10g of brown corundum at 80rpm for 5min, add 20g of gradient mullite-coated SiC particles and continue dry-mixing at 120rpm for 8min; add 10g of coke powder and dry-mix for 7min; heat 6g of zirconium oxide sol-modified phenolic resin to 55℃ and melt, mix with 6g of asphalt and wet-mix at 150rpm for 10min; add 0.2g of dispersant and 0.3g of defoaming agent and stir at 200rpm for 3min, inject into the mold and press at 15MPa, and cure at 180℃ for 5h.

[0058] Example 3: The specific preparation method is the same as Example 1, except that 10 g of zirconia sol-modified phenolic resin, 30 g of gradient mullite-coated SiC particles, 25 g of high-alumina clinker, 15 g of brown corundum, 5 g of coke powder, 3 g of asphalt, 0.5 g of dispersant, and 0.5 g of defoamer are used. Preparation of the zirconia sol-modified phenolic resin: 10 g of phenol and 9.5 g of aqueous formaldehyde solution are mixed, 0.28 g of NaOH solution (25%) is added, and the mixture is reacted at 72°C for 50 min to obtain a prepolymer. 0.01 g of zirconium n-butoxide is added, the pH is adjusted to 5.5, and the mixture is stirred at 92°C for 100 min. After cooling, the mixture is distilled under reduced pressure (68°C, -0.094 MPa) to obtain 10 g of the modified resin. Preparation of gradient mullite-coated SiC particles: α-SiC particles (30 g, particle size 1.2 mm) were dispersed in Al(OH)3 sol (30 g, SiO2 content 0.5%), 0.6 g of ethyl orthosilicate was added, and after ultrasonic dispersion for 40 min, the mixture was kept at 155°C for 8 h; and calcined at 1050°C for 4 h to obtain 30 g of coated particles. Preparation of splash-proof anhydrous taphole mud: dry-mix 25g of high-alumina bauxite clinker and 15g of brown corundum at 90rpm for 10min, add 30g of gradient mullite-coated SiC particles and continue dry-mixing at 140rpm for 10min; add 5g of coke powder and dry-mix for 6min; heat 10g of zirconium oxide sol-modified phenolic resin to 60℃ and melt, mix with 3g of asphalt and wet-mix at 200rpm for 20min; add 0.5g of dispersant and 0.5g of defoamer and stir at 250rpm for 5min, inject into the mold, press at 15MPa, and cure at 190℃ for 8h.

[0059] Comparative Example 1

[0060] The specific preparation method is the same as that of Example 1, except that 25 g of ordinary uncoated SiC particles are used (instead of the gradient mullite-coated SiC particles), steps B1-B2 are omitted, and ordinary SiC particles are directly used for dry mixing.

[0061] Comparative Example 2

[0062] The specific preparation method is the same as that of Example 1, except that 5 g of zirconia sol-modified phenolic resin, 25 g of gradient mullite-coated SiC particles, 30 g of high-alumina bauxite clinker, 12 g of brown corundum, 7 g of coke powder, 5 g of asphalt, 0.3 g of dispersant, and 0.4 g of defoamer are used. The zirconia sol-modified phenolic resin is prepared by adjusting the amount of NaOH solution (0.13 g) and zirconium n-butoxide (0.007 g) based on 5 g of prepolymer.

[0063] Comparative Example 3

[0064] The specific preparation method is the same as that of Example 1, except that 7 g of asphalt, 8 g of zirconium oxide sol-modified phenolic resin, 25 g of gradient mullite-coated SiC particles, 30 g of high-alumina bauxite clinker, 12 g of brown corundum, 5 g of coke powder, 0.3 g of dispersant, and 0.4 g of defoamer are used. 7 g of the asphalt in S2 is used for mixing with the resin.

[0065] Performance Testing

[0066] The materials prepared in Examples 1-3 and Comparative Examples 1-3 were tested for performance according to the following method:

[0067] 1. High-temperature bonding strength (1000°C hot flexural strength): According to GB / T 3002-2013 "Test method for high-temperature flexural strength of refractory materials", the taphole clay is made into a standard specimen of 40mm×40mm×160mm. After curing at 180°C for 8 hours, it is placed in a box furnace and heated to 1000°C at a rate of 10°C / min. It is kept warm for 2 hours, and then a load of 0.2MPa is applied along the length direction. The maximum load when the specimen breaks is recorded, and the flexural strength is calculated (strength = load × span / cross-sectional area, span is 120mm).

[0068] 2. Thermal shock resistance (number of water cooling cycles at 1000°C): According to GB / T 30873-2014 "Test method for thermal shock resistance of refractory materials", the sample after being kept at 1000°C for 2 hours was quickly immersed in 25°C running water (flow rate ≥ 1m / s) and quenched for 3 minutes. After taking out, observe whether there are cracks on the surface; repeat the above process until the sample has a through crack and record the number of cycles.

[0069] 3. Resistance to slag erosion (slag penetration depth): Referring to GB / T 8931-2008 "Test method for slag resistance of refractory materials", the sample after being kept at 1000℃ for 2h was placed in a corundum crucible and covered with blast furnace final slag with a thickness of 5mm (composition: CaO 45%, SiO2 35%, Al2O315%, MgO 5%). After keeping at 1500℃ for 3h, it was cooled and cut along the height direction of the sample. The penetration depth of the interface between the slag layer and the taphole mud was observed using a scanning electron microscope (SEM) (measuring the vertical distance from the edge of the slag layer to the surface of the original taphole mud).

[0070] 4. Effect of molten iron splash suppression: Simulating the working conditions of the blast furnace taphole, 500℃ molten iron (composition: Fe 95%, C 4%, Si0.5%, Mn 0.3%) was impacted on the taphole clay sample (size 40mm×40mm×20mm) at a flow rate of 5m / s. The splashing process was recorded with a high-speed camera (frame rate 1000fps), and the splashing height (the maximum vertical distance of the molten iron from the taphole clay surface) and splashing time (the time from the first splashing to the stop) were measured.

[0071] 5. Curing time: record the time from the completion of stirring of the taphole mud (the slurry is uniform and free of lumps) to pressing and molding (no rebound under a pressure of 15MPa), as well as the time when the surface hardness reaches Shore D 60 after demoulding (tested with a Shore D hardness tester).

[0072] 6. Density: According to GB / T 5072-2008 “Test method for density of refractory materials at room temperature”, grind the cured sample to a size of 20mm × 20mm × 20mm, measure the volume by the Archimedes displacement method, and calculate the density (density = mass / volume).

[0073] 7. Performance test results:

[0074] Table 1: Performance test results of various embodiments and comparative examples

[0075]

[0076] As can be seen from Table 1, through comparative analysis with Comparative Examples 1-3, Examples 1-3 of the present invention significantly address the core issues of anhydrous taphole mud at high temperatures, namely, the susceptibility to pyrolysis of the binder, a sudden drop in bonding strength, and difficulty in inhibiting molten iron penetration. Specifically, in terms of high-temperature binder pyrolysis and bonding strength, the high-temperature bonding strengths (1000°C hot flexural strength) of Examples 1-3 were 7.8 MPa, 6.5 MPa, and 8.2 MPa, respectively, significantly higher than the 4.2 MPa, 5.1 MPa, and 7.1 MPa of Comparative Examples 1-3. This is because the zirconium oxide sol-modified phenolic resin delays resin pyrolysis through the Zr-OC covalent bond network, avoiding the sudden drop in bonding strength caused by the rapid pyrolysis of traditional phenolic resins above 800°C. At the same time, the mullite phase on the surface of the gradient mullite-coated SiC particles forms a continuous interface with the matrix, enhancing the aggregate-matrix bonding and further stabilizing the structural strength at high temperatures. In terms of thermal shock resistance and structural stability, Examples 1-3 achieved thermal shock resistance (number of 1000°C water cooling cycles) of 24, 18, and 26, significantly exceeding the 8, 12, and 19 for Comparative Examples 1-3. The gradient structure of the gradient mullite coating (SiO2 transition layer, mullite coating) effectively alleviates thermal stress concentration and reduces microcrack propagation during thermal shock. The Zr-OC bonds of the modified resin remain stable at high temperatures, preventing interfacial debonding. Together, these factors maintain the structural integrity of the taphole clay during intense thermal shock cycles (ΔT ≈ 800-1000°C). Regarding molten iron penetration suppression, Examples 1-3 achieved slag penetration depths of only 0.3mm, 0.5mm, and 0.2mm (compared to 1.8mm, 1.2mm, and 0.4mm for Comparative Examples 1-3), and the molten iron splash height was 0mm (compared to 8mm, 5mm, and 1mm for Comparative Examples 1-3). At high temperatures, the mullite phase in the gradient mullite coating reacts with CaO in the slag to form high-melting-point anorthite (CaO·Al2O3·2SiO2), forming a dense permeation barrier. Simultaneously, the high high-temperature carbon residue rate of the modified resin forms a continuous carbonaceous barrier on the taphole mud surface. These two factors synergistically hinder the formation of a low-melting-point slag permeation layer, fundamentally suppressing the penetration and splashing of molten iron. In summary, Examples 1-3, through the synergistic effect of zirconium oxide sol-modified phenolic resin and the gradient mullite coating SiC particles, simultaneously address the three core issues of high-temperature binder pyrolysis, bond strength degradation, and molten iron penetration, significantly improving the overall performance of anhydrous taphole mud.

[0077] The above-described embodiments merely illustrate several implementations of the present invention. While the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the spirit of the present invention, and all such variations and improvements fall within the scope of protection of the present invention.

Claims

1. A splash-proof anhydrous taphole mud, characterized in that: The invention comprises the following raw materials in parts by weight: Zirconia sol modified phenolic resin: 6-10 parts by weight; Gradient mullite-coated SiC particles: 20-30 parts by weight; High alumina clinker: 25-35 parts by weight; Brown corundum: 10-15 parts by weight; Coke powder: 5-10 parts by weight; Asphalt: 3-6 parts by weight; Dispersant: 0.2-0.5 parts by weight; Defoaming agent: 0.3-0.5 parts by weight; The preparation method of the zirconium oxide sol-modified phenolic resin includes: A1, adding phenol and formaldehyde aqueous solution in a mass ratio of 1:(0.9-1) to a reactor equipped with a reflux condenser, adding NaOH solution under mechanical stirring, and heating to 70-72°C for reaction to obtain a linear phenolic resin prepolymer; A2, adding zirconium n-butoxide to the reactor, adjusting the pH to 5.0-5.5, heating to 90-92°C for reaction with stirring; after the reaction is completed, cooling to room temperature, adding deionized water for dilution, and performing reduced pressure distillation; The preparation method of the gradient mullite-coated SiC particles includes: B1, dispersing α-SiC particles in Al(OH)3 sol, adding ethyl orthosilicate, ultrasonically dispersing, and then transferring to a hydrothermal reactor for heat preservation at 150-155°C; B2, removing the hydrothermal particles and calcining them in a muffle furnace at 1000-1050°C.

2. The anti-splash anhydrous taphole mud according to claim 1, characterized in that: In step B1, the particle size of the α-SiC particles is 0.5-1.2 mm; the SiO2 content in the Al(OH)3 sol is ≤0.5%; the ethyl orthosilicate accounts for 1.5-2% of the SiC mass; the ultrasonic dispersion time is 30-40 minutes; and the insulation time is 6-8 hours.

3. The anti-splash anhydrous taphole mud according to claim 1, characterized in that: In step B2, the calcination time in the muffle furnace is 2-4 hours.

4. A method for preparing splash-proof anhydrous taphole mud according to any one of claims 1 to 3, characterized in that the steps include: S1. First, add high-alumina bauxite clinker and brown corundum into a forced mixer and dry mix; Add the gradient mullite-coated SiC particles and continue dry mixing; S2. Add coke powder and dry mix; heat the zirconium oxide sol-modified phenolic resin to 55-60°C until it melts, mix it evenly with asphalt, add it to the mixer, and wet mix it until the resin completely covers the aggregate and fills the gaps between the particles; S3. Finally, add the polycarboxylate dispersant and the silicone defoamer, and stir until the slurry is uniform and free of lumps; inject the stirred material into the mold, press it into shape at a pressure of 15-16 MPa, and solidify it at 180-190°C after demolding.

5. The preparation method according to claim 4, characterized in that In step S1, the rotation speed of dry mixing is 80-90 rpm, and the dry mixing time is 5-10 minutes; the rotation speed of continued dry mixing is 120-140 rpm, and the continued dry mixing time is 8-10 minutes.

6. The preparation method according to claim 4, characterized in that In step S2, the dry mixing time is 5-10 minutes; the mass ratio of the zirconium oxide sol-modified phenolic resin to the asphalt is (2-2.5):1 and they are mixed evenly; the wet mixing speed is 150-200 rpm and the time is 10-20 minutes.

7. The preparation method according to claim 4, characterized in that In step S3, the stirring speed is 200-250 rpm, the stirring time is 3-5 minutes, the mold size is 40 mm×40 mm×160 mm, and the curing time is 5-8 hours.

Citation Information

Patent Citations

  • Preparation method of SiO2-mullite-Al2O3 gradient outer coating for carbon / carbon composite material

    CN101898906A

  • No-water stemming material for blast furnace taphole and its prepn

    CN1810723A